Trends and characteristics of COVID-19 and cardiovascular disease related studies - Cheng, Ao; Ren, Honghao; Ma, Zeyao; Alam, Naqash; Jia, Linying; Liu, Enqi (Frontiers in Pharmacology, 2023)
Introduction: The new coronavirus has caused a pandemic that has infected hundreds of millions of people around the world since its outbreak. But the cardiovascular damage caused by the new coronavirus is unknown. We have analyzed the current global scenario and the general pattern of growth. After summarizing the known relationship between cardiovascular diseases and new coronary pneumonia, relevant articles are analyzed by bibliometrics and visualization. Methods: Following our pre-designed search strategy, we selected publications on COVID-19 and cardiovascular disease in the Web of Science database. In our relevant bibliometric visualization analysis, a total of 7,028 related articles in the WOS core database up to October 20th, 2022 were summarized, and the most prolific authors, the most prolific countries, and the journals and institutions that published the most articles were summarized and quantitatively analyzed. Results: SARS-CoV-2 is more infectious than SARS-CoV-1 and has significant involvement in the cardiovascular system in addition to pulmonary manifestations, with a difference of 10.16% (20.26%/10.10%) in the incidence of cardiovascular disease. The number of cases increases in winter and decreases slightly in summer with changes in temperature, but the increase in cases tends to break out of seasonality across the region as mutant strains emerge. The co-occurrence analysis found that with the progress of the epidemic, the research keywords gradually shifted from ACE2 and inflammation to the treatment of myocarditis and complications, indicating that the research on the new crown epidemic has entered the stage of prevention and treatment of complications. Conclusions: When combined with the current global pandemic trend, how to improve prognosis and reduce human body damage could become a research focus. At the same time, timely detection, prevention, and discovery of new mutant strains have also become key tasks in the fight against the epidemic, and full preparations have been made to prevent the spread of the next wave of mutant strains, and still need to continue to pay attention to the differential performance of the variant "omicron."